Literasi keuangan syariah pada generasi Z: Peran keluarga dan religiusitas - Dina Patrisia; Abror Abror (Jurnal Kajian Manajemen Bisnis, 2022)
The high level of islamic financial literacy in the youth generation is expected to encourage the development of the Islamic economy in Indonesia. This study aims to investigate the level of Islamic financial literacy in generation Z as well as the influence of communication patterns in the family, financial socialization, and religiosity in increasing the financial literacy of generation Z. Data collection was carried out using a questionnaire instrument with convenience sampling data collection methods through social media. The total sample consists of 741 respondents who are generation Z from all over Indonesia. Data analysis was performed using structural equation modeling based on variance partial least square (PLS). The results of the study show that the level of Islamic financial literacy of generation Z is still low. Islamic financial literacy is positively and significantly influenced by communication patterns in the family, financial socialization, and religiosity. In addition, financial socialization in the family can mediate the influence of communication patterns in the family on Islamic financial literacy.